Vaccine hesitancy in East Malaysia (Sabah): A survey of the national covid-19 immunisation programme - Adi Jafar; Mohammad Tahir Mapa; Nordin Sakke; Ramli Dollah; Eko Prayitno Joko; Colonius Atang; Syahruddin Awang Ahmad; Chong Vun Hung; Fionna Geogre (PAGEPress, 2021)
The Malaysian government has introduced the National COVID-19 Immunisation Programme (PICK) as a new mechanism to address the transmission of coronavirus disease 2019 (COVID-19). Unfortunately, the number of PICK registrations is still unsatisfactory and is now even lower. The low level of participation of the Sabah (East Malaysia) population significantly impacts the PICK registrations. Therefore, this study aims to identify the factors that cause vaccine hesitancy among the people of Sabah. This study seeks to identify these trends based on zone and district boundaries. A total of 1024 respondents were sampled in this study. Raw data collected through the survey method were analysed using K-means clustering, principal component analysis (PCA), and spatial analysis. The study discovered that factors including confidence, authority, mainstream media, complacency, social media, and convenience are the top causes of vaccine hesitancy among respondents. This study also revealed that the Sabah population’s key variables causing vaccine hesitancy to vary by region (zones and districts). The conclusion is significant as a source of supporting data for stakeholders seeking to identify the Sabah population’s constraints in each region and therefore, it would help improve PICK management’s performance in Sabah.